Digital Academics as Strengthening Religious Moderation Values in Overcoming the Potential of Identity Politics in The Kadokan Village Community, Sukoharjo District - Mahfiyana, Layyin; Ariyani, Evi; Rahmatullah, Lutfi; Yufidz Anwar Ibrohim , Mohammad (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2024)
This community service aims to investigate the role of digital academics in strengthening the values of religious moderation as a response to the potential for identity politics in the community of Kadokan Village, Sukoharjo Regency. Identity politics is often a source of tension and conflict in various communities, especially in religious contexts. A qualitative approach was used in this research by collecting data through in-depth interviews, participant observation, and content analysis of digital platforms used by academics and local communities. The results of UIN Raden Mas Said's Community Service (PKM) regarding